Late Roman to Late Byzantine/Early Islamic Period Lamps in the Holy Land - Sussman, Varda.
1 online resource (643 pages)
Keywords: This volume illustrates lamps from the Byzantine period excavated in the Holy Land and demonstrates the extent of their development since the first enclosing/capturing of light (fire) within a portable man-made vessel.